THE USE OF TALKING CHIPS TO IMPROVE THE SPEAKING SKILL OF THE EIGHTH-GRADE STUDENTS OF SMP NEGERI 2 MENGWI IN THE ACADEMIC YEAR 2021/2022 - Ni Putu Wulan Dewayanti; Putu Ayu Paramita Dharmayanti; Ida Bagus Nyoman Mantra (Academic Journal on English Studies (AJOES), 2023)
In the academic year 2021–2022, this study seeks to enhance the speaking abilities VIII class students of SMP Negeri 2 Mengwi, particularly in presenting daily activities utilizing the talking chips method. In order to get preliminary data about students' speaking abilities, this study began by interviewing English teachers. Prior to the pre-test, the first step was taken to assess the level of the students' speaking abilities, which was found to be low. To help children develop their speaking abilities, the talking chips method was adopted. This study had two cycles, each of which had a pre-test. The average score on the first cycle pre-test was 47.66, which suggested that the students' speaking abilities were not very advanced. However, the score increased to 66.67 in the second cycle pre-test after the talking chips approach was used in the first cycle. Even so, some kids continue to have trouble with their speaking abilities. To confirm that pupils' speaking abilities were improving, a second cycle was conducted. The average score on the second cycle post-test was 78.09, which was a considerable improvement in the students' speaking abilities. The researchers also employed a questionnaire as a research tool to collect extra data. The findings of the survey revealed that students' reactions were favorable following instruction in the talking-chips method. According to the findings of this study, class VIII students at SMP Negeri 2 Mengwi can effectively improve their speaking abilities by using the talking chips technique in the academic year 2021–2022.